Hemoglobin as a mediator between air pollution and growth outcomes in children under 60 months: the moderating role of nutritional supplementation - Xingyi Jin; Di Wu; Fei Ge; Dan Cui; Ayidana Jumabieke; Xiaoli Wang; Rui Wang; Niannian Wang; Jihan Sun; Wang Liao; Da Pan; Li Shao; et al. (BMC Public Health)
Abstract Background Prior research has yielded incongruent results about the association between air pollutants and offspring hemoglobin levels, as well as between air pollutants and child development. This may be because previous studies have not taken both air pollution and nutrition into account. This study sought to examine the correlations between postnatal exposure to air pollution (PM2.5, PM10, SO2, and CO), offspring hemoglobin levels, stunting, and underweight. Furthermore, we investigated whether hemoglobin levels mediate these connections and assessed the moderating influence of dietary supplementation on hemoglobin levels and growth outcomes. Methods A unified nutrition package intervention study was conducted in western, China between 2016 and 2023. In accordance with WHO guidelines, stunting, underweight, height-for-age z score (HFA), weight-for-age z score (WFA), and anemia status were all defined. A daily average of PM2.5, PM10, SO2, and CO levels was collected from the National Urban Air Quality Real-Time Dissemination Platform ( http://www.cnemc.cn/sssj/ ) of the China Environmental Monitoring General Station. Linear regression and logistic regression models were used to assess the correlation between air pollution and the above indicators. The mediating role of hemoglobin and the moderating effect of nutritional supplementation were also evaluated. Findings This study examined the impact of postnatal air pollution exposure on child growth, mediated by hemoglobin levels and moderated by nutritional supplementation (YingYangBao, YYB). Our findings suggest that air pollution negatively affects growth via reduced hemoglobin levels, but extended nutritional supplementation mitigates this effect. A total of 10,766 children under 5 years of age participated in this study. All four air pollutants were associated with reduced hemoglobin levels, but their effects on growth and development were not uniform. Specifically, PM2.5 and PM10 showed stronger negative associations with HFA and WFA, while SO2 and CO had weaker effects. Air pollution had a greater impact on growth outcomes in anemic children compared to non-anemic children. Hemoglobin levels mediated 13.4% of the effect of air pollution on HFA (VAF = 13.4%, Cohen’s f² = 0.15). Furthermore, the duration of YYB moderates the effects of air pollution on hemoglobin and HFA. The direct negative effect of air pollution on HFA was attenuated when the duration of use was > 10 months, whereas in the low use group the pollution effect was enhanced (β=-0.0444, 95%CI: -0.0613, -0.03). Conclusion Postnatal exposure to air pollution (PM2.5, PM10, SO2, CO) increases the risk of stunting, particularly during the critical developmental window of 6–23 months of age. This effect is partially mediated by hemoglobin levels, and YYB can moderate this relationship. These findings highlight the importance of prolonged nutritional interventions in mitigating the adverse effects of air pollution on child growth and development, with significant implications for public health policies targeting air quality and child nutrition in high-pollution regions.